Interprofessional education: shared learning for collaborative, high-quality care. (2nd February 2019) - Power, Alison
Abstract : 'Working together for patients' is a core NHS value that aims to provide high quality care and a well-trained, cohesive workforce. Landmark reports have highlighted how poor interprofessional communication and teamwork can have devastating implications for standards of care and service user outcomes. By embedding interprofessional education (IPE) into the undergraduate curriculum, health and social care students are supported to develop the required knowledge, skills and attitudes to make a positive contribution to the interprofessional team, both as students and as qualified practitioners. This article will give an overview of the drivers for IPE in the UK and look at the challenges of developing an authentic IPE 'collaborative curriculum' using the University of Northampton as a case study.